A Corpus-Based Transitivity Analysis of Khushwant Singh’s Train to Pakistan - Azhar, Wardah; Aslam, Iqra; Aslam, Rukhsar (University of Chitral Journal of Linguistics and Literature, 2023)
Transitivity, a linguistic concept, pertains to the grammatical property of a word in terms of the number of arguments it can take. It holds significance in linguistics by aiding in comprehending sentence structure and the interrelation between word categories. This study explores the utilization of transitivity in Khushwant Singh's inaugural novel. Employing Halliday's Systemic Functional Language (SFL) as the theoretical framework, a transitivity analysis of Train to Pakistan was conducted. The primary objective was identifying the principal transitivity elements in Khushwant Singh's novels.Quantitative analysis, facilitated by the UAM corpus tool, was employed to measure the percentage and frequency of processes. The study's findings indicate that Khushwant Singh's writing style leans towards heightened expressiveness of emotion in characters, with a notable inclination towards participant usage at 29.89% in the novel Train to Pakistan. Examining clause types reveals a prevalent use of material processes, constituting 14.99% of the novel.In conclusion, the study suggests that Khushwant Singh strategically emphasized transitivity processes in Train to Pakistan to illuminate the characters' experiences during the partition. This emphasis highlights the role of actions and relationships in shaping the narrative, offering insights into how historical events impact individuals in the author's stories.